(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The Italian Constitutional Court is called to decide about the constitutional legitimacy of the provision of the penal code concerning aid to suicide (article 580). The author reflects on the existence of a "right to be killed" in the Italian legal system. She doesn’t find this right in the plot of the constitutional principles, and she hopes, on the one side, for a clarifying intervention of the Constitutional court on the correct interpretation of article 580; on the other, for a public reflection and a political decision on the fate of terminally ill or incurable people, who can neither let themselves die nor commit suicide.